A controlled discrete-time queueing system as a model for the orders of two competing companies - Mario Lefebvre (Games, 2024)
We consider two companies that are competing for orders. Let X1(n) denote the number of orders processed by the first company at time n, and let τ(k) be the first time that X1(n)
Keywords: 330; difference equations; dynamic programming; first-passage time; homing problem; linear equations